Antibiotic Potential of Defense Peptides Derived from the Seeds of aWild Grass - Barnyard Grass (Echinochloa crusgalli L.) - E. A. Rogozhin; A. N. Smirnov (Антибиотики и Химиотерапия, 2020)
The article evaluates the inhibitory effect of peptide complexes derived from barnyard grass (Echinochloa crusgalli L.) seeds belonging to various families of plant RP proteins (defensins, lipidtransfer proteins, protease inhibitors of Bowman-Birktype, and bifunctional inhibitors of trypsin/alpha-amylase derived from grasses) and harpino-like peptides (alpha-harpinins) on a number of opportunistic mycelial fungi of the Aspergillus genus by the «alveolar» method, as well as bactericidal effect towards GramPositive bacterium Staphylococcus aureus with the use of flow cytometry and photometry.The primary antifungal effect was observed with respect to the culture collection of fungi-micromycetesof Aspergillus spp. (A.oryzae, A.niger, A.terreus, A.nutans), which was expressed in quantitative suppression of hyphal growth and conidia germination. Only the EcLTP peptide had a statistically significant bactericidal action.The data obtained, on the one hand, allow us to consider this wild grass as a potential donor of highly active polypeptides used for protection of cultivated monocotyledonous plants from diseases caused by specific fungal pathogens, and, on the other hand, as a source of next-generation natural peptide antibiotics.